Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae) - Freyhof, Jörg; Kaya, Cüneyt; Bayçelebi̇ Esra; Geiger, Matthias; Turan, Davut (Zootaxa, 2018)
The generic position of Leuciscus kurui Bogutskaya, 1995 is reviewed through a comparison of morphological and molecular characters (COI). The molecular data place L. kurui in Alburnus, close to Alburnus timarensis from the Lake Van basin. Alburnus kurui (Bogutskaya) is distinguished from this species by lacking a ventral keel and possessing both a very low number of gill rakers and midlateral scales. Alburnus selcuklui, from the upper Tigris drainage, cannot be distinguished from the widespread A. sellal and is therefore treated as a synonym of this species. Alburnus kurui Mangit & Yerli, 2018 is a junior secondary homonym of A. kurui (Bogutskaya, 1995) and A. carianorum is proposed as its replacement name. Several specimens of Alburnus caeruleus and Alburnus heckeli shared the same haplotypes as some A. sellal and therefore these species cannot always be distinguished by mitochondrial molecular characters. Alburnus caeruleus and A. heckeli are treated as valid species. Other individuals of A. caeruleus have haplotypes very different from A. sellal, and A. heckeli is well distinguished from A. sellal by having more gill rakers. The Lake Van basin as a separate freshwater ecoregion and the treatment of several species of Alburnus in synonymy of A. mento are discussed.